2010
DOI: 10.1021/ja105850d
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Formation of I−I Bonds Using DNA Which Enables Detection of Single Nucleotide Polymorphisms

Abstract: By decreasing the HOMO energy gap between the base-pairs to increase the charge conductivity of DNA, the positive charge photochemically generated in DNA can be made to migrate along the π-way of DNA over long distances to form a long-lived charge-separated state. By fine-tuning the kinetics of the charge-transfer reactions, we designed a functionalized DNA system in which absorbed photon energy is converted into chemical energy to form I-I covalent bonds, where more than 100 I(2) molecules were produced per f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…19,21,62,78 The increasing distance between ATTO 655 and Z resulted in an exponential increase of τ FCS . Charge recombination proceeds within 1 μs for b4 due to the close distance between Z and ATTO 655, is clearly observed for b5, and in the case of b6, τ FCS becomes too long and indistinguishable from the diffusion process ( Figure 7D).…”
Section: Journal Of the American Chemical Societymentioning
confidence: 99%
“…19,21,62,78 The increasing distance between ATTO 655 and Z resulted in an exponential increase of τ FCS . Charge recombination proceeds within 1 μs for b4 due to the close distance between Z and ATTO 655, is clearly observed for b5, and in the case of b6, τ FCS becomes too long and indistinguishable from the diffusion process ( Figure 7D).…”
Section: Journal Of the American Chemical Societymentioning
confidence: 99%
“…Since a hole moves much faster through a consecutive A-T sequence rather than through an A-T/T-A repeat sequence due to the closer distance and direct stacking between As [18], the inversion of the A-T base-pair in an A-T stretch was expected to decrease the Φ. Interestingly, the inversion of the A-T basepair adjacent to NI led to an increase in Φ (NTA1) in spite of the unfavorable 1 The electron transfer from NI radical anion to bromouridine dose not takes place in less than 100 μs (see [58]). …”
Section: Charge-separation Triggered By Hole-injection Into the Seconmentioning
confidence: 99%
“…Some Gs within the consecutive G-C base-pairs were replaced with deazaguanine (Z), which have a lower oxidation potential than G (0.98 V vs NHE) [30,[56][57][58], to refine the charge-separation process to achieve a larger Φ. Hence, DNAs were designed so as to have an (A-T) n (n ¼ 0 À 5) spacer and an (X-C) 3 (X¼G or Z) charge pathway between Sens and PTZ.…”
Section: •àmentioning
confidence: 99%
“…DNA duplexes can also transport holes and excess electrons over a distance,323 and such charge‐transfer reactions in DNA might be involved in the recognition of damaged DNA bases by DNA repair enzymes 24. In addition, it has been demonstrated that electron‐transporting DNA could be used as a device for genotyping and for single‐nucleotide polymorphism analysis 2529…”
mentioning
confidence: 99%